Operationalizing transformative capacity: State policy and the financing of sustainable energy transitions in developing countries - Amanda-Leigh O'Connell; Johan Schot (Green Finance)
We explored the capacity of the state to facilitate financing for sustainable energy transitions in a developing country context. We responded to the critical challenge of financing in developing and emerging contexts where significant financing gaps contribute to the inequitable deployment of renewable energy technologies. A critical realist case study design explored South Africa's transition to green hydrogen as an instrumental case to understand how policy instruments—regulative, economic, and informational—interact with financing social structures to enable or constrain transformative change in financing the energy transition. The conceptual framework drew on sustainability transitions literature and integrated insights from finance, policy, and institutional theories to operationalize the state's transformative capacity in modifying financing rules through policy interventions. Data was collected through semi-structured interviews with key stakeholders and analysis of academic and grey literature, including policy documents and government publications. The findings illustrated how policy instruments can reinforce, disrupt, transform, or displace structures, embodying varying degrees of the state's capacity to engender structural change. Critically, the findings support transition scholars who advocate for experimental policy engagements by offering opportunities to challenge fundamental values, norms, beliefs, and cognitive models.